Role of neurturin in spontaneous itch and increased nonpeptidergic intraepidermal fiber density in a mouse model of psoriasis. Issue 11 (November 2017) - Sakai, Kent; Sanders, Kristen M.; Youssef, Marina R.; Yanushefski, Kevin M.; Jensen, Liselotte E.; Yosipovitch, Gil; Akiyama, Tasuku
Abstract : Abstract: Psoriasis is often accompanied by itch, but the mechanisms behind this symptom remain elusive. Dynamic changes in epidermal innervation have been observed under chronic itch conditions. Therefore, we investigated whether epidermal innervation is altered in the imiquimod-induced psoriasis mouse model, whether blockade of neurotrophic growth factor signaling can reduce these changes, and whether this system can impact psoriatic itch. Over the 7-day time course of imiquimod treatment, the density of epidermal nonpeptidergic nerves significantly increased, whereas the density of peptidergic nerves significantly decreased. The nonpeptidergic epidermal nerves expressed glial cell line–derived neurotrophic factor (GDNF) family receptor GFRα-1 and GFRα-2, the ligand-binding domains for GDNF and neurturin (NRTN). The NRTN mRNA expression was elevated in the skin of imiquimod-treated mice, whereas the GDNF mRNA expression was decreased. Treatment of imiquimod-challenged mice with an NRTN-neutralizing antibody significantly reduced nonpeptidergic nerve density as well as spontaneous scratching. These results indicate that NRTN contributes to an increase in the epidermal density of nonpeptidergic nerves in the imiquimod-induced psoriasis model, and this increase may be a factor in chronic itch for these mice. Therefore, inhibition of NRTN could be a potential treatment for chronic itch in psoriasis. Abstract : The imiquimod-induced psoriasis mouse model exhibited increased density of epidermal nonpeptidergic nerves. Neurturin inhibitor reduced nonpeptidergic nerve density as well as spontaneous itch.